2015
DOI: 10.1021/acsami.5b05531
|View full text |Cite
|
Sign up to set email alerts
|

Facile Preparation of Water-Dispersible Graphene Sheets Stabilized by Carboxylated Oligoanilines and Their Anticorrosion Coatings

Abstract: Dispersion of graphene in solvents is of crucial importance toward its practical applications. In this study, using a water-soluble carboxylated aniline trimer derivative (CAT(-)) as a stabilizer, the commercial graphene can be stably dispersed in water at high concentration (>1 mg/mL) via strong π-π interaction that was proved by Raman and UV-vis spectra. Moreover, the CAT(-)-functionalized graphene sheets (G-CAT(-) hybrid) exhibited high conductivity (∼1.5 S/cm), good electroactivity and improved electrochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
102
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 220 publications
(102 citation statements)
references
References 34 publications
0
102
0
Order By: Relevance
“…A higher R ct implied less number of corrosive electrolytes were transported into coatings . As seen in Table , R ct was increased with addition of material because of the barrier function of the coating was gradually being exerted . Meanwhile, the value of R pore for RGO‐IL coating was higher than sore RGO sample which can be explained by the good dispersity of RGO in coating and improving coating electrical resistance against transfer of corrosive species through the pores of coating.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…A higher R ct implied less number of corrosive electrolytes were transported into coatings . As seen in Table , R ct was increased with addition of material because of the barrier function of the coating was gradually being exerted . Meanwhile, the value of R pore for RGO‐IL coating was higher than sore RGO sample which can be explained by the good dispersity of RGO in coating and improving coating electrical resistance against transfer of corrosive species through the pores of coating.…”
Section: Resultsmentioning
confidence: 96%
“…[49] As seen in Table 2, R ct was increased with addition of material because of the barrier function of the coating was gradually being exerted. [50] Meanwhile, the value of R pore for RGO-IL coating was higher than sore RGO sample which can be explained by the good dispersity of RGO in coating and improving coating electrical resistance against transfer of corrosive species through the pores of coating. CPE dl as constant phase of the double layer was the non-ideal capacitance between the working electrode and coating, while the charge transfer resistance R ct was in parallel with CPE dl , which showed that the electrolyte permeates at the surface of Q235.…”
Section: The Eis Measurements For Various Coatingsmentioning
confidence: 95%
“…EIS is a rapid, in situ and non-destructive technique for investigating the electrochemical properties of the electrode surface and affording information on the impedance changes of the electrode surface during the modification process [16,17]. Figure 4 illustrated the Nyquist diagrams and Bode plots of the CuO-graphene cathode under different reduction potentials in 10 g/L Na 2 SO 4 solution.…”
Section: Preparation and Characterization Of Cuo-graphene Cathodementioning
confidence: 99%
“…[14] Recently, considerable amount of papers have reported that the graphene/polymer composite possesses enhanced barrier properties that are beneficial for high anticorrosion performances. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Unlike carbon nanotubes that can only provide similar mechanical benefits, [10] these lightweight sheets can reduce oxygen permeability of host membranes. [15,31] It also should be noted that the graphene process outstanding electrical conductivity, [32][33][34] which can increase the conductivity of coatings when doped into the polymer matrixes.…”
Section: Introductionmentioning
confidence: 99%